DUSP26 regulates podocyte oxidative stress and fibrosis in a mouse model with diabetic nephropathy through the mediation of ROS - Huang, Feng; Sheng, Xu-Xiang; Zhang, Hong-Juan (Biochemical and biophysical research communications, 2019)
Diabetic nephropathy (DN) is a leading cause of renal failure worldwide. Unfortunately, the pathogenetic mechanism of DN is far from to be understood. Dual-specificity phosphatase 26 (DUSP26) is a member of the Dusp protein family, and is suggested to be involved in divers biological and pathological processes, such as cell growth, differentiation, inflammation and apoptosis. However, its role in the development of DN is still vague. In this study, we found that DUSP26 expression was increased in kidney of DN patients. Then, the wild type (DUSP26+/+) and gene knockout (DUSP26−/−) mice were used to further explore the effects of DUSP26 on DN development induced by streptozotocin (STZ). DUSP26 deficiency accelerated renal injury and dysfunction, as evidenced by the elevated glomerulosclerosis, reduced expression of Nephrin and promoted glomerular basement membrane thickness. In addition, STZ treatment resulted in reactive oxygen species (ROS) accumulation, H2O2 overproduction and superoxide dismutase (SOD) reduction in renal cortex or glomeruli of mice. The ROS production caused the activation of mitogen-activated protein kinase (MAPKs) signaling in kidney glomeruli of STZ-induced mice. These in vivo pathological processes were further confirmed in the differentiated podocytes stimulated by glucose (GLU). Intriguingly, we found that STZ-induced DN as mentioned above was further accelerated by DUSP26−/− in mice following STZ injection. Moreover, STZ-induced fibrosis in kidney glomeruli of DN mice was markedly prolonged in DUSP26-knockout mice through potentiating transforming growth factor-β1 (TGF-β1) expression. More importantly, reducing ROS generation could significantly abolish DUSP26 knockdown-exacerbated TGF-β1 expression and MAPKs activation, thereby protecting podocytes from GLU-induced podocyte injury. Thus, DUSP26-regulated DN development was largely dependent on ROS generation. Taken together, we concluded that DUSP26 might be a promising therapeutic target for developing effective treatments against DN progression. ➢DUSP26 knockout promotes podocyte injury in diabetic nephropathy (DN) mice.➢DUSP26 inhibition enhances podocyte ROS production and MAPKs activation in DN mice.➢DUSP26 knockout regulates podocyte fibrosis in DN mice through controlling ROS production.